Secondary thrombosis prevention practice patterns in pediatrics: Results of an international survey - Hope P. Wilson; Rosebella Capio; Inmaculada Aban; Jeffrey Lebensburger; Neil A. Goldenberg (Research and Practice in Thrombosis and Haemostasis, 2022)
Abstract Background Pediatric venous thromboembolism (VTE) rates continue to increase. Although most children present with transient provoking factors, some have persistent prothrombotic risks beyond the initial treatment period warranting secondary anticoagulation. Current pediatric VTE guidelines provide limited recommendations in this regard. Objectives Our primary objective was to identify key influences on pediatric thrombosis physicians’ decisions to initiate secondary anticoagulation. Methods We targeted pediatric hematologists/oncologists internationally using Duration of Therapy for Thrombosis in Children, Children’s Hospital Acquired Thrombosis consortium, and Venous Thromboembolism Network US pediatric subgroup membership rosters, who self‐identified as primary outpatient thrombosis providers. Of 124 total surveys distributed, 61 complete surveys were evaluable. We defined secondary anticoagulation as anticoagulant use beyond the initial treatment period, on a daily basis (extended) or limited to periods of superimposed clinical risk factors (episodic). Results Pediatric thrombosis physicians surveyed indicated that they prescribe secondary anticoagulation in <25% of children despite persistent risks. Among those who indicated use of secondary anticoagulation, the preferred modality was extended anticoagulation in children with a history of recurrent unprovoked VTE (98%), chronic central venous catheter (74%), and potent thrombophilia (73%). Episodic anticoagulation was preferred in children with a history of mild thrombophilia (54%). Respondents were more likely to prescribe secondary anticoagulation for adolescents as opposed to children <12 years old. Conclusions Among pediatric thrombosis physicians surveyed, they perceived the prevalence of persistent prothrombotic risks to be high in children who have completed a course of anticoagulation for provoked VTE; however, estimated use of secondary anticoagulation was low. Studies involving real‐world data are needed to further evaluate use of secondary anticoagulation in this setting.